Housing Finance and Real Estate Markets in Colombia - Roch, Francisco (Washington, D.C. : International Monetary Fund, 2017)
Colombian house prices have increased significantly between 2005 and 2016. This paper estimates the extent of misalignments in house prices relative to fundamentals and evaluates the overall risk to the economy from the housing sector. The results suggest a moderate house price misalignment relative to fundamentals which is, however, mitigated by housing finance characteristics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet